2008
DOI: 10.1063/1.3062849
|View full text |Cite
|
Sign up to set email alerts
|

Work softening and annealing hardening of deformed nanocrystalline nickel

Abstract: We reported that work softening takes place during room-temperature rolling of nanocrystalline Ni at an equivalent strain of around 0.30. The work softening corresponds to a strain-induced phase transformation from a face-centered cubic ͑fcc͒ to a body-centered cubic ͑bcc͒ lattice. The hardness decreases with increasing volume fraction of the bcc phase. When the deformed samples are annealed at 423 K, a hardening of the samples takes place. This hardening by annealing can be attributed to a variety of factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…Several reasons viz. strain induced phase transformation [19], softening due to texture [20], plastic instability and localization in shear bands [21], localized temperature rise due to adiabatic shear banding [22] have been suggested as the reason for flow softening. Here in case of Al-Li alloys, there is no phase transformation.…”
Section: Characteristics Of Flow Curvesmentioning
confidence: 99%
“…Several reasons viz. strain induced phase transformation [19], softening due to texture [20], plastic instability and localization in shear bands [21], localized temperature rise due to adiabatic shear banding [22] have been suggested as the reason for flow softening. Here in case of Al-Li alloys, there is no phase transformation.…”
Section: Characteristics Of Flow Curvesmentioning
confidence: 99%
“…Similar phenomenon has also been found in Cu and Cu-Ge alloys with low to medium SFE [12]. Another mechanical behavior concerning the softening of nc metals is generally observed when strain hardening reaches the maximum level [13][14][15][16][17]. For simplicity, we refer to this cross-over between strain hardening and strain softening as "mechanical transition".…”
Section: Introductionmentioning
confidence: 63%
“…Additional experimental details can be found in Ref. [16]. of the nc samples was investigated by XRD (Rigaku D/MAX 2500 PC, 18 kW) operating in a step scan mode with Cu K␣ radiation.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the pure Ni, the hardness of the current nc Ni-20Fe alloy is greatly improved with the Fe alloying effect, which is known as solid solution hardening [20]. In our previous investigation, the pure nc nickel enters into strain hardening slowly and reaches the peak hardness at an equivalent strain of about 0.30 [21]. Noted that the nc Ni-20Fe alloy reaches a peak hardness just at the equivalent strain of 0.10, it can be concluded that the presence of Fe plays a significant role in the strain hardening.…”
Section: Resultsmentioning
confidence: 97%
“…Noted that strain hardening still takes place in spite of grain coarsening. It has been suggested that plastic flow is dominated by grain rotation and dislocation activity [21,25]. The emission of dislocations from the GB occurs preferentially in the grains with a favorable orientation.…”
Section: Resultsmentioning
confidence: 99%